The Neospora caninum-Spain 7 isolate induces placental damage, fetal death and abortion in cattle when inoculated in early gestation - Caspe, Sergio Gaston; Moore, Prando Dadin; Leunda, Maria Rosa; Cano, Dora Beatriz; Lischinsky, Lilian Haydee; Regidor-Cerrillo, Javier; Alvarez-García, Gema; Echaide, Ignacio Eduardo; Bacigalupe, Diana; Ortega-Mora, Luis; Odeon, Anselmo Carlos; Campero, Carlos Manuel (Elsevier, 2021)
The Nc-Spain 7 isolate of Neospora caninum, which was newly obtained from an asymptomatic congenitally infected calf, demonstrated a similar virulence as Nc-1 strain in mouse models. The aim of this study was to characterize the pathogenesis of Nc-Spain 7 isolate in cattle after experimental infection at 65 days of gestation. For this purpose, thirteen pregnant heifers were divided into three groups as follows: group A: 7 heifers inoculated with 1 × 108 tachyzoites of Nc-Spain 7 isolate; group B: 4 heifers inoculated with 1 × 108 tachyzoites of Nc 1 strain; and group C: 2 heifers received PBS. Serum samples were collected weekly and heparinized blood samples were collected three times (0, 28 and 42 days after inoculation) by jugular venipuncture. Placenta and fetal tissue samples were collected at time of necropsy. Specific antibody response in the dams was tested by IFAT, indirect ELISA, and rNcGRA7 and rNcSAG4 based-ELISA. Specific antibody response in fetal fluids was tested by IFAT. IFN-γ production was measured after in vitro culture of PBMC and the supernatant was assessed using a commercial kit (BOVIGAM). A significant increase in N. caninum antibody responses was detected in groups A and B by IFAT and by i-ELISA from day 14 after inoculation onwards. Besides, antibody response against rNCGra7 protein was also detected in all inoculated heifers by rNcGra7-based ELISA. Four fetuses from group A and one from group B were aborted between 3 and 5 weeks after infection. In the recovered fetuses, only 3 out of 4 fetal fluids from fetuses of group A and 1 out of 3 of group B were seropositive by IFAT, but all of them were positive by PCR. Transplacental transmission could be determined in all fetuses from groups A and B by PCR and/or IHC. Heifers of group C and their fetuses remained negative by all techniques. The results of this study demonstrate that the NC-Spain 7 isolate could be transmitted transplacentally, and produced fetal death and abortion in cattle.